Pengaruh Disiplin Dan Motivasi Terhadap Kinerja Karyawan Pada PT Home Center Indonesia Cabang QBIG BSD Tangerang Selatan - Ahmad Faozan; Retno Japanis Permatasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the simultaneous influence of discipline and motivation on employee performance at PT Home Center Indonesia QBIG BSD Tangerang Branch. The method used is quantitative associative The research population was 101 people who were calculated using the Slovin formula. The data analysis techniques used are instrument testing, classical assumption testing, descriptive analysis, regression testing, correlation coefficient testing, coefficient of determination testing and hypothesis testing. The research results show that the discipline variable partially influences employee performance variables by 69.8%, while the remaining 30.2% is influenced by other variables not studied. Motivation partially influences employee performance by 30.4%, while the remaining 69.6% is influenced by other variables not studied. Discipline and motivation simultaneously influence employee performance variables by 73.1%, while the remaining 26.9% is influenced by other variables not studied. The research results of the multiple linear regression equation Y = 5.086 + 0.635 X1 + 0.241 X2. This means that employee performance, even without the influence of discipline and motivation, already has an influence of 8.429. Simultaneously, discipline and motivation have a positive and significant influence on employee performance, this is proven by the calculated F value > F table, namely (133.079 > 3.09) with a significance of 0.000 < 0.05, so H0 is rejected and H3 is accepted, meaning it can be concluded that positive and significant influence between discipline and motivation on employee performance simultaneously at PT Home Center Indonesia QBIG BSD Tangerang Branch.